DEVELOPMENT OF GEOPOLYMERS USING FLY ASH AND NANO SILICA FROM PALM ASH FOR COATING STUDY - KHAN, MUHAMMAD IRFAN (2016)
The environmental and health risks of petrochemical derived coatings accompanied by their degradation and failure at high temperatures need to be addressed. In this study, different types of geopolymers were synthesized to investigate the effect of mixed design and nano silica on thermal stability, durability, workability and adhesiveness of geopolymers. Sodium silicate free, sodium silicate based and nano silica incorporated geopolymers were prepared from fly ash and alkali activators.. The agglomeration in silica was controlled by the addition of poly ethylene glycol (MW 20,000); giving nano silica particles in the range of 20-80 run, surface area of 326 nrg"1, and pore diameter of "8~.2~nmTThermokinetics and thermodynamics studies, using the Kissinger, Ozawa and Starink methods, revealed physical interactions between Si02 particles and PEG molecules.